2020
DOI: 10.1038/s41392-020-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of copper-cysteamine nanoparticles to simultaneously enable radiotherapy, oxidative therapy and immunotherapy for melanoma treatment

Abstract: Dear Editor, Melanoma, squamous cell carcinoma (SCC), and basal cell carcinoma (BCC) are three major types of skin cancer. Among them, melanoma is the most severe form and accounts for~4% of all newly diagnosed cancers annually in the United States. It is estimated that approximately 9500 people are diagnosed with skin cancer every day, and more than 1 million Americans are living with melanoma. Melanoma treatment is still a major challenge in the clinic. Photodynamic therapy (PDT) is composed of targeted abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Indeed, in our 2D study, we find that the polyhaemoglobin component of polylactide nanocarrier-polyhaemoglobin increases ROS production [16,17]. Others had also shown that ROS inhibits tumour growth [18]. Our 3D culture studies (Figure 6) also showed that polylactide nanocarrier-polyhaemoglobin has some effect on melanoma cells though not as much as the polylactide nanocarrier-PH-TYR.…”
Section: In Vivo Effects Of Component Polylactide Nanocarrier Polyhaemoglobin (Ncap-ph)supporting
confidence: 62%
“…Indeed, in our 2D study, we find that the polyhaemoglobin component of polylactide nanocarrier-polyhaemoglobin increases ROS production [16,17]. Others had also shown that ROS inhibits tumour growth [18]. Our 3D culture studies (Figure 6) also showed that polylactide nanocarrier-polyhaemoglobin has some effect on melanoma cells though not as much as the polylactide nanocarrier-PH-TYR.…”
Section: In Vivo Effects Of Component Polylactide Nanocarrier Polyhaemoglobin (Ncap-ph)supporting
confidence: 62%
“…It was found that these Cu-Cy nanoparticle-based X-PDT exhibited a remarkable antitumor effect towards SCC. However, B16F10 melanoma was resistant to these Cu-Cy nanoparticle based X-PDT, both in vitro and in vivo [49], whereas the 40 nm Cu-Cy nanoparticles are very effective in inhibiting melanoma under X-ray stimulation [50]. This could be due to the fact that the 40 nm Cu-Cy nanoparticles have a larger surface area, thereby producing more ROS and the cellular uptake is higher for the 40 nm nanoparticles [18].…”
Section: Discussionmentioning
confidence: 98%
“…Also the induction of adequate immune responses after photo tumor ablation may be fundamental to obtain a long term therapeutic effect of phototherapy. For this reason, Zhu et al projected the photosensitizer chlorin e6 (Ce6) and the well-known immunoadjuvant aluminum hydroxide into bovine serum albumin by biomineralization as a novel nanosystem (Al-BSA-Ce6 NPs) [ 92 ]. After intravenous injection, the nanoparticles were able to destroy tumor cells effectively and, at the same time protect animals against tumor rechallenge and metastasis by strongly inducing a systemic anti-tumor immune response.…”
Section: Nanotechnologies and Immunotherapy In Melanomamentioning
confidence: 99%